Preface to the Special Issue on “Advances in Artificial Intelligence: Models, Optimization, and Machine Learning” - Florin Leon; Mircea Hulea; Marius Gavrilescu (Mathematics, 2022)
Recent advancements in artificial intelligence and machine learning have led to the development of powerful tools for use in problem solving in a wide array of scientific and technical fields [...]